The Ritual Aspects Of Customary Law In Sarawak With Particular Reference To The Iban - Langub, Jay'l (Journal of Malaysian and Comparative Law, 1998)
We like to think of ourselves as rational individuals. We believe ourselves able to choose our own way of life, untrammeled by the often superstitious and irrational beliefs and practices of tradition. Indeed, many even believe that tradition should be set aside in favour of progress and development.